2009
DOI: 10.1111/j.1538-7836.2008.03217.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines and the use of inferior vena cava filters: a review of an institutional experience

Abstract: Summary.  Background and objectives: Based on the American College of Chest Physicians 2004 antithrombotic therapy for venous thromboembolism (VTE) and the Eastern Association for the Surgery of Trauma 2002 guidelines, placement of an inferior vena cava (IVC) filter is indicated in patients who either have, or are at high risk for, VTE, but have a contraindication or failure of anticoagulation. Our aim is to compare clinical characteristics and outcomes of patients receiving IVC filters within‐guidelines (WG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…8 In a more recent single centre study, placement of IVC filters in patients with VTE approximately doubled between 2004 and 2007. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In a more recent single centre study, placement of IVC filters in patients with VTE approximately doubled between 2004 and 2007. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in several studies rates of removal of temporary IVC filters have been quite low (5–20%) suggesting that most of these devices are in fact permanent. 16, 17 …”
Section: Discussionmentioning
confidence: 99%
“…These authors concluded that IVC filter placement outside of guidelines was not warranted. 18 White et al 19 did a population-based study comparing outcomes after acute VTE in 3,632 patients who had filter placement with 64,333 patients who did not receive an IVC filter. The incidence of recurrent PE at 1 year did not differ between the groups, but the incidence of rehospitalization for venous thrombosis was higher in the patients receiving an IVC filter if they initially presented with a PE.…”
Section: Discussionmentioning
confidence: 98%
“…18 Singh et al found in their retrospective study of patients receiving prophylactic filters either within EAST guidelines or outside of guidelines that only the patients within guidelines derived benefit from the procedure. 19 This emphasizes the importance of defining a high-risk population that will derive benefit from prophylactic IVC filter placement.…”
Section: Traumamentioning
confidence: 99%